Technological Training and Teaching Digital Competences (Docentes 2.0 Journal, 2021)
The health contingency has led everyone to voluntary home confinement. Therefore, digital skills development is a primary issue in the educational field, mainly due to the current situation due to the pandemic. Consequently, it is significant to establish the relationship between the technical training received and the digital teaching competencies of primary education teachers. In the diagnosis of a qualitative-quantitative exploratory study in progress, the perception that primary education teachers of the Adventist Educational System of Campeche have of their technical training and their digital teaching skills were valued, where 68 teachers answered an online questionnaire of 10 items. The results showed that most participants acquired their technological knowledge on their initiative and believed they were prepared to use technology in their daily teaching work. However, only 58.8% indicated using it in instruction and 47.1% in collaboration. On the other hand, in the four dimensions of the digital teaching competence, they are perceived at a high intermediate level; only in "Creation of digital content" was a perception of a low intermediate level obtained. The findings indicate that there are discrepancies between the specialized training received and the digital teaching competence used in instructional practice. The urgency of aligning the training of teachers is concluded, designing a permanent systematic model to meet their requirements to improve their pedagogical approach.
Keywords: Teachers’ digital competencies; elementary education; technological training